The impact of land legislation on farm dweller evictions - Mntungwa, Dumisani (My University, 2014)
Eviction of farm dwellers by farmers and landowners in post-Apartheid South Africa has increased at an alarming rate. The consequences of being evicted can be devastating for the livelihood of farm dwellers as it is often accompanied by the loss of work, income and homes, the loss of access to land for food production, generating urban slums and displacement areas not within reach of municipal basic services as well as other negative effects such as the breakdown of family and social structures and disruptions to children’s education. Plus land security is important for poor farm dwellers usage to produce their own food and complement low farm wages. The livelihood strategies of farm dwellers have been affected by the introduction of the 1997 Extension of Security tenure legislation, which aims at protecting and restoring the land rights of farm dwellers working in farms. Farmers and landowners responded to legislation reforms by evicting farm dwellers off their land. The ESTA legislation has not been implemented effectively and has failed to restore the land rights of evicted farm dwellers and protect those facing the risk of eviction. It has only served to disadvantage those it was supposed to protect. It is therefore important to protect those made worse off by legislation and identify factors keeping the poorest farm dwellers vulnerable and struggling to survive. The research would focus on the impact of the Extension of Security Tenure land legislation on farm dwellers evictions in selected areas of Mogale and Randfontein Local Municipalities under the Westrand region in Gauteng.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Political Studies, 2014